Integrated Modeling Approach to Predict the Morphodynamic Impacts of the Boğaçay Project on Konyaaltı Beach - Akiner, Muhammed Ernur (Three E Science Institute, 2025)
This study examines the effects of the Boğaçay Project, launched in 2017 on the Konyaaltı Coast of Antalya, on shoreline evolution using a multi-model approach. The project interrupted the natural sediment cycle, impacting both short-term morphological changes and long-term coastal stability. This study evaluates these effects through integrated models. Morphological changes from excavations at the estuary cut off natural sediment transport and were integrated with (1) the Pelnard-Considère model for long-term coastal evolution, (2) the SWAT model for basin-scale transport analysis, and (3) the XBeach model for simulating coastal hydrodynamics and morphodynamics. The study employed XBeach-based high-resolution simulations to represent physical processes, elucidate the current situation, and facilitate the testing of shoreline evolution scenarios under various engineering interventions. The model, calibrated using satellite images, coastline data, and topographic scans, showed strong agreement between numerical outputs and observations, thereby enhancing model accuracy. Results indicated an average coastal retreat of 21.7 meters over the 3 years following the project. While artificial sediment feeding slowed regression by 58%, XBeach simulations revealed that the deepened estuary worsened erosion in the east by altering wave dynamics diffraction. This integrated modeling approach highlights the critical role of sediment dynamics in coastal stability, underscoring the need for revised coastal management policies. The study identifies the spatial and temporal dynamics of shoreline changes and simulates the basic morphodynamic processes, predicting the effects of intervention scenarios. This comprehensive modeling enables the development of sustainable management strategies that protect ecosystem integrity and inform engineering solutions in human-degraded coastal systems.